Non-surgical interventions for the treatment of masticatory muscular spasticity in patients with cerebral palsy. Systematic review of randomized clinical trials - Rocha, Monise Mendes; Martimbianco, Ana Luiza Cabrera; Beltramin, Rafael Zaratin; Horliana, Anna Carolina Ratto Tempestini; Santos, Elaine Marcílio; Mesquita-Ferrari, Raquel Agnelli; Fernandes, Kristianne Porta Santos; Motta, Lara Jansiski; Turcio, Karina Helga [UNESP]; Gonçalves, Marcela Leticia Leal; Bussadori, Sandra Kalil (Elsevier, 2022)
Introduction: Muscle disorders caused by cerebral palsy (CP) can affect oral function. The treatment for masticatory muscle spasticity is important to minimize muscle hyperactivity and preclude oral damages. Objectives: To evaluate the efficacy and safety of non-surgical interventions for the treatment of masticatory muscle spasticity in CP patients. Methods: A comprehensive search was performed in the following databases: MEDLINE, Embase, Cochrane Library, LILACS, BBO, PEDro, Clinicaltrials.gov and WHO/ICTRP, without date and language restrictions. Randomized controlled trials (RCT) evaluating non-surgical interventions were considered. Primary outcomes such as masticatory function and adverse events were planned to be assessed. The risk of bias assessment was performed using the Cochrane risk of bias tool. The certainty of the evidence was assessed using the GRADE approach. Results: Three RCT assessing the effects of botulinum toxin, functional masticatory training and neuromuscular electrostimulation (NMES) were included. Evidence with a very low certainty showed: (i) no difference between botulinum toxin and placebo regarding maximum chewing strength, chewing efficiency and global oral health scale; (ii) improvement in masticatory function in favor of functional masticatory training versus conventional exercises, and (iii) in favor of strengthening exercises plus NMES versus placebo. Conclusions: There was insufficient evidence to support the use of botulinum toxin and masticatory muscle strengthening programs alone and associated with NMES for the treatment of masticatory muscle in patients with PC. The clinical decision must be individualized, and further studies are needed to support or refute the use of different non-surgical interventions for PC. PROSPERO register number CRD42020209761.
Keywords: Cerebral palsy; Masticatory muscle; Muscle spasticity; Systematic review